Evaluation of the Elecsys® anti-Müllerian hormone assay for the prediction of hyper-response to controlled ovarian stimulation with a gonadotrophin-releasing hormone antagonist protocol. (May 2019) - Anckaert, Ellen; Denk, Barbara; He, Ying; Torrance, Helen L.; Broekmans, Frank; Hund, Martin
Abstract: Objective: This non-interventional study aimed to validate a pre-specified anti-Müllerian hormone (AMH) cut-off of 15 pmol/L (2.10 ng/mL) for the prediction of hyper-response to controlled ovarian stimulation (COS) using the fully automated Elecsys® AMH immunoassay. Study design: One hundred and forty-nine women aged <44 years with regular menstrual cycles underwent COS with 150 IU/day follicle-stimulating hormone in a gonadotrophin-releasing hormone (GnRH) antagonist protocol. Response to COS (poor vs normal vs hyper-response) was defined by number of oocytes retrieved and occurrence of ovarian hyper-stimulation syndrome (OHSS). Results: Significant differences were seen between response classes for the number of follicles prior to follicle puncture (p < 0.001), the number of retrieved oocytes (p < 0.001) and the occurrence of OHSS (p < 0.001), which were all highest in hyper-responders. The area under the receiver operating characteristic curve for AMH to predict hyper-response was 82.1% (95% confidence interval [CI]: 72.5–91.7). When applying the AMH cut-off of 15.0 pmol/L, a sensitivity of 81.3% (95%CI: 54.4–96.0) to predict hyper-response and a specificity of 64.7% (95%CI: 55.9–72.8) to identify poor/normal responders was reached. Conclusion: The Elecsys® AMH assay can reliably predict hyper-response to COS in women undergoing a GnRH antagonist treatment protocol.